A ROS-responsive, aptamer-targeted graphene oxide nanocomposite for site-specific glutathione release in cerebral ischemia-reperfusion injury - Li, Meiying; Wei, Lili; Liu, Wenxu; Wang, Jiawen; Lu, Qiujie; Chen, Xianjue; Lim, Lee Yong; Mo, Jingxin (Frontiers in Pharmacology, 2025)
Cerebral ischemia-reperfusion (I/R) injury is a major contributor to mortality and long-term disability worldwide, primarily due to excessive reactive oxygen species (ROS) generation after blood flow is restored. Although current treatments focus on reestablishing perfusion, they offer limited protection against the secondary ROS-mediated injury. Here, we report a multifunctional nanocomposite-graphene oxide loaded with glutathione (GSH) and functionalized with a fibrinogen-targeting aptamer (GO@GSH-FA)-capable of selectively releasing antioxidant cargo within the ischemic brain microenvironment. Characterization revealed a drug-loading capacity of 17.59% ± 3.74% and an entrapment efficiency of 78.78% ± 4.55%, highlighting the robust loading of GSH. The ROS-sensitive borate ester linker ensures that GSH is preferentially liberated in oxidative stress regions, while the fibrinogen aptamer actively targets fibrin-rich thrombotic sites. In vitro, GO@GSH-FA significantly restored viability in oxygen-glucose-deprived SH-SY5Y cells (from 31% up to near control levels), reduced inflammatory cytokines, and lowered intracellular ROS. In a Endothelin-1 (ET-1) induced cortical ischemia model, GO@GSH-FA led to a marked decrease in neurological deficit scores (from 7.20 ± 1.16 to 4.20 ± 0.98) and enhanced neuronal survival relative to untreated animals. Collectively, these findings underscore the promise of GO@GSH-FA as a targeted, ROS-responsive platform for mitigating cerebral I/R injury.